Zamboanga [videorecording] child of the sea. ([Quezon City] Philippine Information Agency)
Documents Zamboanga as city of two distinct cultures. It shows the evolution of the different religions in this place.
Keywords: Zamboanga; Geography; Philippine history; Religion